The Role of Islamic Tradition as a Civic Virtue in Environmental Management of Rice Farming in Transmigration Settlements - Reza Adriantika Suntara; Muhamad Hijran; Tri Indrayati (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2026)
Rias Village in the South Bangka Regency has been projected as the settlement of Javanese, Sundanese, and Bugis transmigrants alongside the indigenous Bangka community. The coexistence of these diverse ethnic groups has given rise to variations in social and cultural practices, as well as differences in agricultural management approaches. The role of civic virtue was examined in shaping community life within the transmigration area, with particular attention to traditional practices that contribute to harmonious environmental management. Qualitative-descriptive research was employed, where the data were collected through observation, purposive sampling interviews, and document analysis. Research findings from document studies were analyzed through several stages such as document familiarization, coding process, theme and pattern analysis, interpretation, and report preparation. The findings indicate that three key Islamic traditions like Sedekah Bumi, Maulid Nabi, and Ruwahan embody the principles of civic virtue. These traditions function as mechanisms for fostering unity and social cohesion, while simultaneously supporting collective values of civic disposition and civic commitment. Sedekah Bumi is related to civic disposition in hopes of getting better harvest in the following year. Maulid Nabi fosters civic commitment in building togetherness. The ruwahan tradition fosters civic commitment in building intimacy. The values positively influence the cooperative management of agricultural environments.